Severe acute respiratory syndrome coronavirus 2 pathology and cell tropism in tongue tissues of COVID-19 autopsies - Ma, Longda; Liu, Qian; Wang, Manli; Liu, Liang; Hu, Zhihong; Zhou, Yiwu; Liu, Jia (Frontiers in Cellular and Infection Microbiology, 2024)
Since 2019, Coronavirus Disease 2019(COVID-19) has affected millions of people worldwide. Except for acute respiratory distress syndrome, dysgeusis is also a common symptom of COVID-19 that burdens patients for weeks or permanently. However, the mechanisms underlying taste dysfunctions remain unclear. Here, we performed complete autopsies of five patients who died of COVID-19. Integrated tongue samples, including numerous taste buds, salivary glands, vessels, and nerves were collected to map the pathology, distribution, cell tropism, and receptor distribution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the tongue. Our results revealed that all patients had moderate lymphocyte infiltration around the salivary glands and in the lamina propria adjacent to the mucosa, and pyknosis in the epithelia of taste buds and salivary glands. This may be because the serous acini, salivary gland ducts, and taste buds are the primary sites of SARS-CoV-2 infection. Multicolor immunofluorescence showed that SARS-CoV-2 readily infects Keratin (KRT)7+ taste receptor cells in taste buds, secretory cells in serous acini, and inner epithelial cells in the ducts. The major receptors, angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine subtype 2 (TMPRSS2), were both abundantly expressed in these cells. Viral antigens and receptor were both rarely detected in vessels and nerves. This indicates that SARS-CoV-2 infection triggers pathological injury in the tongue, and that dysgeusis may be directly related to viral infection and cellular damage.